The Role of NMDA Receptors in Alzheimer’s Disease - Liu, Jinping; Chang, Lirong; Song, Yizhi; Li, Hui; Wu, Yan (Frontiers in Neuroscience, 2019)
In Alzheimer’s disease (AD), early synaptic dysfunction is associated with the increased oligomeric amyloid-beta peptide, which causes NMDAR-dependent synaptic depression and spine elimination. Memantine, low-affinity NMDAR channel blocker, has been used in the treatment of moderate to severe AD. However, clear evidence is still deficient in demonstrating the underlying mechanisms and a relationship between NMDARs dysfunction and AD. This review focuses on not only changes in expression of different NMDAR subunits, but also some unconventional modes of NMDAR action.